Profession of Government Minister in Western Europe - Blondel, Jean. author. aut Link
XII, 215 p.
Keywords: Despite the apparent political similarities in Western Europe, the models of cabinet government employed by different nations vary. In exploring the ministerial profession, this text reveals the political traditions and the different needs and expectations of citizen and politician alike.